2019
DOI: 10.3390/md17110642
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Antioxidant Peptide by Microwave- Assisted Hydrolysis of Collagen and Its Protective Effect Against H2O2-Induced Damage of RAW264.7 Cells

Abstract: Antioxidant peptides have elicited interest for the versatility of their use in the food and pharmaceutical industry. In the current study, antioxidant peptides were prepared by microwave-assisted alkaline protease hydrolysis of collagen from sea cucumber (Acaudina molpadioides). The results showed that microwave irradiation significantly improved the degree of hydrolysis of collagen and the hydroxyl radical (OH⋅) scavenging activity of hydrolysate. The content and OH⋅ scavenging activity of collagen peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 37 publications
6
32
0
Order By: Relevance
“…These results indicate that the protective effect of SNNH-1 on H 2 O 2 -induced HUVECs injury may be due to the inhibition of intracellular ROS production. These results are in accordance with the data presented by Li et al [ 22 ], who found that collagen peptides from sea cucumbers ( Acaudina molpadioides ) could effectively protect cells from H 2 O 2 -induced damage.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate that the protective effect of SNNH-1 on H 2 O 2 -induced HUVECs injury may be due to the inhibition of intracellular ROS production. These results are in accordance with the data presented by Li et al [ 22 ], who found that collagen peptides from sea cucumbers ( Acaudina molpadioides ) could effectively protect cells from H 2 O 2 -induced damage.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure 5 , peptide fractions of less than 1 kDa had the highest DPPH free radical scavenging rate compared to the other ultrafiltration fractions. Similar research has shown that the low-Mw content of protein hydrolysates has higher antioxidant activity [ 22 ]. Therefore, fractions with a Mw of less than 1 kDa were chosen for subsequent activity evaluation and named SNNH-1.…”
Section: Resultsmentioning
confidence: 73%
“…However, SNNH-1 pretreatment reduced ROS levels in a concentration-dependent manner on HUVECs cells. These results were in agreement with the data presented by Li et al [ 65 ], who found that collagen peptides from sea cucumbers ( Acaudina molpadioides ) could protect RAW264.7 cells from H 2 O 2 -induced damage. Hu et al [ 58 ] observed the effects of MMP-4, MMP-7, and MMP-12 (three peptides of hydrolysate of monkfish, Lophius litulon, muscle), on the level of ROS in oxidative damage HepG2 cells.…”
Section: Discussionsupporting
confidence: 93%
“…After culturing for 24 h, the medium was gently aspirated and replaced with LPs <1 kDa at different concentrations (12.5, 25, 50, 100, 200, 400, 600, 800, and 1000 μg/mL). Cells were cultured in the medium for 24 h and treated with H 2 O 2 (final concentration of 500 μmol/L) for 8 h [ 38 ]. Then, 20 μL of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) was added into the culture solution.…”
Section: Methodsmentioning
confidence: 99%